Characterization of P. aeruginosa Glucose 6- Phosphate Isomerase: A Functional Insight via In-Vitro Activity Study - Angira, Deekshi; Natarajan, Nalini; Dedania, Samir R; Patel, Darshan H; Thiruvenkatam, Vijay (Current topics in medicinal chemistry, 2020)
Glucose-6-phosphate isomerase (G6PI) catalyses the second step in glycolysis in the reversible interconversion of an aldohexose glucose 6-phosphate, a six membered ring moiety to a ketohexose, fructose 6-phosphate five membered ring moiety. This enzyme is of utmost importance due to its multifunctional role like neuroleukin, autocrine motility factor, etc. in various species. G6PI from Pseudomonas aeruginosa is less explored for its moonlighting properties. These properties can be predicted by studying the active site conservation of residues and their interaction with the specific ligand.BACKGROUNDGlucose-6-phosphate isomerase (G6PI) catalyses the second step in glycolysis in the reversible interconversion of an aldohexose glucose 6-phosphate, a six membered ring moiety to a ketohexose, fructose 6-phosphate five membered ring moiety. This enzyme is of utmost importance due to its multifunctional role like neuroleukin, autocrine motility factor, etc. in various species. G6PI from Pseudomonas aeruginosa is less explored for its moonlighting properties. These properties can be predicted by studying the active site conservation of residues and their interaction with the specific ligand.Here, we study the G6PI in a self-inducible construct in bacterial expression system with its purification using Ni-NTA chromatography. The secondary structure of pure G6PI is estimated using circular dichroism to further predict the proper folding form of the protein. The bioactivity of the purified enzyme is quantified using phosphoglucose isomerase colorimetric kit with a value of 12.5 mU/mL. Differential scanning fluorimetry and isothermal titration calorimetry were employed to monitor the interaction of G6PI with its competitive inhibitor, erythrose 4-phosphate and calculated the Tm, Kd and IC50 values. Further, the homology model for the protein was prepared to study the interaction with the erythrose 4-phosphate. MD simulation of the complex was performed at 100 ns to identify the binding interactions.METHODSHere, we study the G6PI in a self-inducible construct in bacterial expression system with its purification using Ni-NTA chromatography. The secondary structure of pure G6PI is estimated using circular dichroism to further predict the proper folding form of the protein. The bioactivity of the purified enzyme is quantified using phosphoglucose isomerase colorimetric kit with a value of 12.5 mU/mL. Differential scanning fluorimetry and isothermal titration calorimetry were employed to monitor the interaction of G6PI with its competitive inhibitor, erythrose 4-phosphate and calculated the Tm, Kd and IC50 values. Further, the homology model for the protein was prepared to study the interaction with the erythrose 4-phosphate. MD simulation of the complex was performed at 100 ns to identify the binding interactions.We identified hydrogen bonds and water bridges dominating the interactions in the active site holding the protein and ligand with strong affinity.RESULTSWe identified hydrogen bonds and water bridges dominating the interactions in the active site holding the protein and ligand with strong affinity.G6PI was successfully crystallized and data has been collected at 6Å. We are focused on improving the crystal quality for obtaining higher resolution data.CONCLUSIONG6PI was successfully crystallized and data has been collected at 6Å. We are focused on improving the crystal quality for obtaining higher resolution data.